Effects of Oats (Avena sativa L.) on Inflammation: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Kim, Sun Jo; Jung, Cheol Woon; Anh, Nguyen Hoang; Kim, Suk Won; Park, Seongoh; Kwon, Sung Won; Lee, Seul Ji (Frontiers in Nutrition, 2021)
Background: Oat and its compounds have been found to have anti-inflammatory effects. Through this systematic review and meta-analysis, we aimed to determine an evidence-based link between oat consumption and inflammatory markers. Methods: The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines were followed. By the end of April 2021, we included randomized controlled trials (RCTs) that investigated the anti-inflammatory effect of oat and oat-related products through screening PubMed, Embase, Web of Science, ClinicalTrial.gov, and CENTRAL. Meta-analysis was conducted with a random-effect model on the standardized mean difference (SMD) of the change scores of inflammatory markers, including C-reactive protein (CRP), tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6), and interleukin-8 (IL-8). Subgroup analyses were conducted to stratify confounding variables. The risk of bias was evaluated using the Cochrane risk of bias tool and Grading of Recommendations, Assessment, Development and Evaluation (GRADE) was applied to report the quality of evidence. This study was registered in the International Prospective Register of Systematic Reviews (PROSPERO; CRD42021245844). Results: Systematic screening of five databases yielded 4,119 studies, of which 23 RCTs were finally selected. For the four systemic inflammatory markers analyzed, no significant alterations were found after oat consumption. However, oat intake was found to significantly decrease CRP levels in subjects with one or more health complications (SMD: −0.18, 95% CI: −0.36, 0.00; P = 0.05; I2 = 10%). Furthermore, IL-6 levels were significantly decreased in subjects with dyslipidemia (SMD = −0.34; 95% CI: −0.59, −0.10; P = 0.006; I2 = 0%). These beneficial effects might be attributed to the effects of avenanthramide and β-glucan. Conclusions: Overall evidence supporting the alleviation of inflammatory response by oat intake was poor, calling for future studies including a larger sample size to confirm the findings.